Effect of a care process programme on frail older people's life satisfaction - Helene Berglund; Susanne Gustafsson; Isabelle Ottenvall Hammar; Joel Faronbi; Synneve Dahlin‐Ivanoff (Wiley, 2019)
Abstract Aim The aim of this study was to analyse the effects of a full‐scale implementation of a care process programme on life satisfaction among frail older people, as compared with those receiving usual care. Design The study includes participants from a full‐scale care process programme (N = 77) and participants from a historical control group (N = 66). The care process programme establishes a comprehensive continuum of care through components including case management, interprofessional teamwork and care‐planning meetings in the older people's own homes. Methods Questionnaires were used and data were collected at baseline, with follow‐ups at three, six and 12 months. Results The implementation of the full‐scale care process programme had a positive effect on life satisfaction among frail older people. From 6‐month-12‐month follow‐ups, a higher proportion of participants in the care process programme had positive life satisfaction outcomes, as compared with the historical control group.